Decapod assemblages in subtidal and intertidal zones—Importance of scuba diving as a survey technique in tropical reefs, Brazil - Giraldes, Bruno Welter (2015)
Decapods play a crucial role within the reef ecosystem and the development of scuba diving as a survey tool has allowed researchers the opportunity to study the decapod–reef relationship more comprehensively. The present study describes the differences in decapod assemblages in intertidal and subtidal zones at a tropical coastal reef system in the southwestern Atlantic Ocean and reports the importance of scuba diving as a survey technique. A total of 71 decapods were recorded during the research; 42 in the intertidal zone mainly formed by small endobenthic species and 39 in the subtidal zone primarily large species only 10 were found to frequent both sample zones. The study extends the range of Brachycarpusholthuisi Fausto Filho 1966 in Brazil; and also demonstrates how scuba diving can be used to complement traditional methodologies and vice versa. The research shows the advantages of using scuba diving when studying trade endangered decapods, as the methodology allows access to cryptic habitats such as reef caves and underwater cavities which were inaccessible when using traditional techniques. In conclusion scuba diving represents a revolutionary non-destructive survey tool allowing the researcher to directly access a specific decapod assemblage in fragile reef environments and in protected marine areas.